Research status of subclinical hypothyroidism promoting the development and progression of cardiovascular diseases - Peijie Wang; Weiming Zhang; Haiyan Liu; Haiyan Liu (Frontiers in Cardiovascular Medicine)
In recent years, the incidence of cardiovascular disease (CVD) has risen steadily, significantly impacting public health. Subclinical hypothyroidism (SCH) remains a controversial risk factor for CVD. This review examines the associations between SCH and dyslipidemia, carotid intima-media thickness (C-IMT), cardiac dysfunction, and cardiovascular event risk. Evidence suggests SCH may exacerbate atherosclerosis and cardiac dysfunction through mechanisms such as increased LDL synthesis, oxidative stress, and impaired vascular endothelial function. However, the causal link between SCH and cardiovascular outcomes remains unclear due to study design heterogeneity and overreliance on TSH levels. Elevated TSH may not solely reflect thyroid dysfunction but could also indicate compensatory responses to inflammation, aging, or stress. Large-scale studies like NHANES and IPD meta-analyses show a strong association between SCH and cardiovascular risk in younger populations, which diminishes in older adults due to physiological TSH increases. The cardiovascular benefits of levothyroxine (L-T4) therapy in SCH patients are limited, especially in older individuals, where a narrow therapeutic window increases side effect risks. Studies relying solely on TSH as a diagnostic and therapeutic target have significant limitations, as TSH cannot distinguish adaptive thyroid adjustments from pathological states and overlooks the role of free thyroid hormones (FT3/FT4). Future research should integrate multi-dimensional markers (such as oxidative stress indicators, vascular elasticity measures, and thyroid antibody status) and adopt longitudinal study designs to more accurately assess the clinical significance of SCH.